PREFERENCES OF DOCTORS FOR WORKING IN RURAL ISLAMABAD CAPITAL TERRITORY, PAKISTAN: A QUALITATIVE STUDY - Rana, Sana Azmat; Sarfraz, Mariyam; Kamran, Irum; Jadoon, Huma (Journal of Ayub Medical College Abbottabad, 2016)
Background: Developing countries are faced with acute shortages of human resources in rural/remote areas. Decision of human resources for health to work in rural areas are influenced by many financial and non-financial factors. This study focused on preferences of doctors for working in rural and resource constrained areas of Pakistan. Methods: The study was based on qualitative research techniques. Focus group discussions (FGDs) were conducted with final year medical students and house officers and In-depth Interviews (IDIs) with senior health managers of Islamabad Capital Territory (ICT). Results were analyzed using qualitative content analysis technique to present the findings. Results: The results showed that quality of facilities, career development, lack of incentives, quality of life, and lack of connectivity between rural and urban health facilities, transportation services and governance issues are some of the main factors identified by young doctors of ICT that contribute in their decision of choosing a certain job or not in rural areas. Conclusion: Study results show the in-depth detail of deciding factors for attracting and retaining health workforce in rural areas. These can be used for designing DCE (Discrete Choice Experiment) questionnaire to further analyze the preference incentive packages for attracting doctors to work in rural Islamabad. Keywords: Human resource; Job Preferences; Rural Islamabad